Spectral approaches to nutrient stress detection in pineapple cultivation on a tropical peat soil - Chong, Yen Mee (2017)
Pineapple in Malaysia is largely cultivated on peat which has resulted in problems including poor drainage, low fertility, subsidence and irreversible drying which rarely occurred on mineral soil. Hence, replenishment of nutrients and organic matter to soil through rational fertiliser application is part of the precision agriculture practices to enhance soil quality and crop productivity. To further avoid excessive application of fertilisers, a study was conducted to measure the reflectance changes of nutrient stress induced by nitrogen (N) and potassium (K) deficiencies, using a spectroradiometer. While other parameters such as growth measurement including height, leaf width and leaf number were made at 45, 135 and 225 days after planting, alongside with leaf nitrogen content measurement with hand-held Minolta SPAD-502 chlorophyll meter. Four different levels of nitrogen and potassium were applied to the pot as Urea (46 % N) and Muriate of Potash (60 % K2O) respectively. All suckers of MD2 variety were pre-treated with fungicide before potted on raised beds in double row, spaced 0.6 m x 0.6 m on the bed and 0.9 m apart within row in a randomised complete block design. The fertilisers were applied at three split periods of 3-, 5- and 8-month after planting [N0 (control with no fertiliser added); N1 (369 kg/ha); N2 (528 kg/ha); N3 (686 kg/ha); K0 (control with no fertiliser added); K1 (256 kg/ha); K2 (366 kg/ha); K3 (476 kg/ha). Other fertilisers were applied equally for all pots either via broadcast or micronutrient fertiliser spray. In this study, several published indices were used to evaluate their capabilities to quantify leaf N concentration of pineapple grown under four contrasting levels of N & K. Results showed that different vegetation indices were found most useful depending on crop phenology. The three indices, the Narrow Band Normalised Difference Vegetation Index (NBNDVI), Greenness Index (GI) and Nitrogen Reflectance Index (NRI) performed better at differentiating N rates from mid to advanced growth stages. While the Normalised Difference Red Edge Index (NDRE) performed equally well but at more advanced growth stage and the Normalised Difference Vegetation Index (NDVI) was the least performing index with greater sensitivity to N stress in young plant rendering it ineffective in present study focusing on mid to advance growth stages of pineapple. On the other hand, K deficiency tested reported three out of six indices evaluated in this study to be effective at differentiating K rates across varying growth stages. The Normalised Pigment Chlorophyll Index (NPCI) and Plant Senescence Reflectance Index (PSRI) were found to be useful throughout the entire study period, while the Red Edge Vegetation Stress Index (RVSI) only showed minimal differences between K rates. The other three indices including NDRE, NDVI and NBNDVI were found to be ineffective in K study. Additionally, canopy reflectance of K-deficient pineapple also exhibited a shift of red edge towards shorter wavelengths of 500-700 nm as often observed in the absence of N. The results ascertained that canopy and leaf reflectance changes are important indicators of fertiliser application. The changes of canopy and leaf reflectance may show whether the plant has received sufficient nutrients, so that fertiliser can be applied at appropriate amount without being wasted.